Analysis of Educational Marketing Strategies Through Social Media to Increase New Student Interest - Dian Ardiansah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
The development of information technology has changed many aspects of life, including education. One significant impact is the use of social media and websites as the primary means of marketing various educational programs. Although MTS N 2 Pangandaran already has various accounts on various social media platforms such as Facebook with the account name